Development of a novel and viable knock-in factor V deficiency murine model: Utility for an ultra-rare disease - Juan A. De Pablo-Moreno; Leopoldo González-Brusi; Andrea Miguel-Batuecas; Pablo Bermejo-Alvarez; Luis Revuelta; Antonio Liras (PLoS ONE, 2025)
Factor V deficiency is a congenital coagulation disorder characterized by the absence or malfunction of factor V (FV). The purpose of this study was to develop a viable FV-deficient mouse model using CRISPR/Cas9 technology. A viable pathological model of the disease was not available to develop new therapies. A previous in silico study was performed to select a mutation causing a mild disease phenotype in humans (Thr1898Met missense). Such mutation was replicated in mice by CRISPR-mediated homology directed repair. Following crossing, homozygous individuals were subjected to coagulometry assays, including FV levels, prothrombin time (PT), and activated partial thromboplastin time (aPTT). The in silico study suggested that the mutation destabilizes FV structure of both mouse and human variants, putatively producing a mild phenotype of the disease in mice. Mendelian inheritance was observed in the offspring. No spontaneous signs of blood clotting disturbances, premature deaths or gestational dysfunctions were observed. FV levels in homozygous animals were 24.5% ± 5.1; 39.7 sec ± 2.8; PT was 61.8% ± 6.3; 23.4 sec ± 1.6 (INR = 1.47 ± 0.12); and aPTT was 46.9 sec ± 3.2. A viable FV-deficient mouse model was generated by introducing a missense mutation in FV. The model exhibits a mild phenotype of the disease, akin to that observed in humans.